Improvement and Nocturnal Extension of the Efficiency of a Solar Still - Mandi, B. (Hindawi Limited, 2021)
Various studies have been made to improve the efficiency of the solar still. These studies had devoted to the combination of solar collectors with solar still. This article proposes the use of all forms of solar thermal or photovoltaic energy. In addition, photovoltaic electric storage systems convert them to thermal energy that increases the temperature of a greenhouse solar still. We investigated the possibility of improving the productivity of a greenhouse still and prolong solar distillation overnight. The proposed system is the incorporation of thermal energy produced by a parabolic-cylindrical concentrator, a greenhouse still, and photovoltaic solar energy by panels. The production at 14 pm reaches 110 L/m2 thanks to the various thermal sources made up of the hybrid still. It has better productivity than other distillers. The distillation is extended in the evening thanks to a storage system using electric batteries. The production at 18 pm to 18 L/m2 is reduced at 24 pm to 5 L/m2 in the dark. The accumulated temperature decreases the negative influence of the physical parameters on the production which exceeds 100 L/m2 per day. In the evening, the production is reached 16 L/m2 at 22 pm, which is an advantage compared to other distillers. Â© 2021 Benaissa Mandi et al.